Tuberculous meningitis: role of CT in management and prognosis. Issue 1 (January 1987) - Kingsley, D P; Hendrickse, W A; Kendall, B E; Swash, M; Singh, V
Abstract : Serial computed tomographic scans were performed during the course of tuberculous meningitis in 25 patients aged 1-70 years. Hydrocephalus rarely occurred without other abnormalities. Marked ventricular enlargement was associated with extensive basal enhancement. Basal meningeal enhancement was not a good indicator of the clinical state although marked enhancement was a risk factor for the development of basal ganglia infarction. Infarcts were much more common in children than in adults and were sometimes asymptomatic. Radiological abnormalities sometimes developed during treatment and often did not resolve completely. Many patients had severe residual neurological problems.